Validação do diagnóstico de enfermagem regulação do humor prejudicada em pessoas idosas com sintomas depressivos - Brito, Fabiana Medeiros de (2021)
Introduction: The indicators of the NANDA-I Impaired mood regulation nursing diagnosis might not be pertinent to the phenomenon if the experiences of older people with depressive symptoms in our sociocultural context are considered. Aim: To validate the NANDA-I Impaired mood regulation nursing diagnosis in older people with depressive symptoms. Method: Methodologic study guided by the Hoskins’ nursing diagnosis validation model: concept analysis and expert validation. In the conceptual analysis, the model proposed by Walker and Avant were applied as well as the methodological stages of the integrative literature review. In order to reach the validation, expert nurses who deal with the said nursing diagnosis in their caring practice were invited. The data was collected via a questionnaire with information related to the nursing diagnosis elements under analysis, in which experts rated the pertinence of such elements as clinical evidence of the diagnosis based on a 4-point Likert scale that goes from not pertinent to completely pertinent. Data analysis was carried out on the basis of a qualitative approach through descriptive statistics of all variables. To do so, a computational system and also the Statistical Package for the Social Sciences – SPSS, 20.0 version, were used, since it meets the scope of the research goals. The study operationalization occurred after its approval by the Ethics Committee of the Health Sciences Center of the Federal University of Paraiba. Results: In the concept analysis stage, new elements were identified (revised definition, defining characteristics, related factors, and associated conditions) when it comes to the nursing diagnosis under analysis, in addition to the existent elements described at NANDA-I, which were defined in the theoretical and operational scope. In the expert’s evaluation stage, 14 defining characteristics, 12 related factors, and 3 associated conditions were identified as pertinent to the diagnosis, as well as 7 new indicators, categorized as population at risk. Considering the total scores of the analyzed diagnosis of 0,72 related to the expert’s validation phase, it is safe to say that the Impaired mood regulation diagnosis validation, according to the experts that were consulted, was assessed as adequate. At last, the following theoretical definition of the Impaired mood regulation nursing diagnosis was developed: a dynamic and multidetermined condition of mood or affection swings, variable in severity, that inflicts biopsychosocial and functional harm on elderly people affected by it. Conclusion: The study developed here is pioneering the Impaired mood regulation nursing diagnosis when it comes to the reality experienced by Brazilian nurses who are experts in the area. Besides that, it represents a significant contribution to the research, teaching, and nursing practice areas. It is important to draw attention to the fact that the nursing diagnosis validation studies are extremely important to the concept refinement, in the sense that it guides clinical reasoning in nursing, as well as the formulation of therapeutic plans directed to the reality of older people going through depressive symptoms and mood swings.